2018
DOI: 10.1029/2017jc013618
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Residual Current in the Seto Inland Sea Driven by Sea Level Difference Between the Bungo and Kii Channels

Abstract: Understanding residual (i.e., total minus tidal) currents in coastal seas is important because the residual currents affect long‐term material transports. In the Seto Inland Sea, Japan (SIS), a Bungo Channel to Kii Channel sea level difference causes a horizontal pressure gradient in the SIS and thus affects the residual current in the SIS. This study applies a linear regression method to examine how the residual current responds to the Bungo‐Kii sea level difference. The residual current is obtained using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The variation of the net volume transport is almost in phase with the SSH difference between the Bungo and Kii Channels (Fig. 2b), suggesting that the pressure difference between the channels drives the throughflow, as pointed out by previous studies 3–5 . These characteristics are also the same for TIDE (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The variation of the net volume transport is almost in phase with the SSH difference between the Bungo and Kii Channels (Fig. 2b), suggesting that the pressure difference between the channels drives the throughflow, as pointed out by previous studies 3–5 . These characteristics are also the same for TIDE (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Previous studies 3,4 suggested that the sea level difference between the Bungo and Kii Channels drive the throughflow. Based on the same data of the above direct measurement 2 , it is also pointed out that the sea level difference causes variation in the volume transport of the throughflow 5 . Figure 1b shows the sea level difference estimated from the sea surface height (SSH) of high-resolution reanalysis data (FORA-WNP30 6 ).…”
Section: Introductionmentioning
confidence: 92%
“…Sensors 2019, 19, x FOR PEER REVIEW 2 of 15 observations with multi-station networking, which is a prominent advantage in comparison with fixed-point and sensor array measurements [10][11][12][13][14]. A significant number of experiments have been conducted to measure range-average temperatures or map temperature distribution vertically and horizontally with CAT [15][16][17][18].…”
Section: Inversion Methodsmentioning
confidence: 99%
“…It was developed as a coastal application of the ocean acoustic tomography technique [ 9 ]. CAT can conduct real-time field observations with multi-station networking, which is a prominent advantage in comparison with fixed-point and sensor array measurements [ 10 , 11 , 12 , 13 , 14 ]. A significant number of experiments have been conducted to measure range-average temperatures or map temperature distribution vertically and horizontally with CAT [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an application of ocean acoustic tomography (OAT) in coastal areas, coastal acoustic tomography (CAT) has emerged as a new observation technology [8,9]. It could achieve a large range of velocity and temperature field observations and meet the long-term, real-time requirements of the field observations needed [10,11,12,13,14]. Underwater Wireless Sensor Network (WSN) can also achieve temperature field observations.…”
Section: Introductionmentioning
confidence: 99%